Sutureless Electrocautery-Assisted Excision of a Recurrent Giant Earlobe Keloid Following Piercing: A Case Report - Dian Andriani Ratna Dewi; Juliandra Firdaus; Khufitha Tasya (The ASEAN Journal of Military and Preventive Medicine, 2026)
Background: Auricular keloids represent challenging fibroproliferative scars frequently induced by ear piercing and are characterized by a high recurrence rate, especially following repeated surgical interventions. In cases of recurrent earlobe keloids, minimizing further trauma and wound tension is critical to reducing the likelihood of subsequent recurrence. Case illustration: A 22-year-old woman presented with a recurrent, giant keloid on the right earlobe subsequent to ear piercing. The lesion had progressively enlarged over a 10-year period, despite four prior surgical interventions and corticosteroid injections. Clinical examination identified a firm, raised, pinkish keloidal mass measuring 7 × 5 × 3 cm. Electrocautery-assisted excision and debulking were performed under local and tumescent anesthesia. The wound was deliberately left unsutured to prevent additional puncture trauma, foreign-body reaction, and wound-edge tension. Postoperative care included local wound management, topical antibiotic and tulle dressings, and pressure therapy, facilitating healing by secondary intention. Discussion: Electrocautery enabled controlled tissue removal with simultaneous hemostasis and minimal manipulation of surrounding skin. Avoiding primary suturing was considered important because suture-related dermal trauma and tension may reactivate abnormal fibroblast activity in keloid-prone tissue. Combined with pressure therapy, this sutureless approach supported gradual wound remodeling. Conclusion: Electrocautery-assisted sutureless excision, followed by secondary intention healing and pressure therapy, may serve as an alternative strategy for selected cases of recurrent giant earlobe keloids. No clinical recurrence was observed at 12-month follow-up.